Hello(adsbygoogle = window.adsbygoogle || []).push({});

In textbook by Kobayashi and Nomizu derivation of rank k in space of all differential forms on a manifold is defined to be operator that is linear, Leibnitz and maps r-forms into r+k-forms. By Leinbitz I mean, of course: [itex]D(\omega \wedge \eta)=(D \omega) \wedge \eta + \omega \wedge (D \eta)[/itex]. Skew-derivation is defined similarly, but rather than Leibnitz property it satisfies: [itex]D(\omega \wedge \eta)=(D \omega) \wedge \eta + (-1)^r \omega \wedge (D \eta)[/itex], where [itex]\omega[/itex] is r-form.

Then claim is made that if [itex]D[/itex] is derivation of rank k and [itex]D'[/itex] is skew-derivation of rank k' then [itex][D,D'][/itex] is skew-derivation of rank k+k'. However, formula which I'm getting (just by using the properties given) is:

[tex][D,D'] ( \omega \wedge \eta )= \left\{ ( [D,D'] \omega) \wedge \eta + (-1)^r \omega \wedge ([D,D'] \eta) \right\} +(-1)^r (1-(-1)^k) (D \omega) \wedge (D' \eta)[/tex]

Term outside of curly brackets vanishes only for k even, so as far as I understand, claim given by K&N holds only then. If anyone has an idea what could have gone wrong (or is it possible that there is an error in K&N), please help. Thanks in advance.

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Lie bracket of derivations in space of r-forms

Loading...

Similar Threads - bracket derivations space | Date |
---|---|

I Lie bracket on a manifold | Sep 9, 2017 |

I Prove what the exterior derivative of a 3-form is... | Apr 11, 2016 |

Lie derivative of tensor field with respect to Lie bracket | Sep 14, 2015 |

Controllability of non-linear systems via Lie Brackets | Nov 19, 2014 |

Covariant derivative of Lie-Bracket in normal orthonormal frame | Dec 6, 2011 |

**Physics Forums - The Fusion of Science and Community**